Leptospirosis as a cause of acute respiratory failure: clinical features and outcome in 35 critical care patients - Vieira,Silvia R R (2002)
Leptospirosis may have important complications, such as acute respiratory failure (ARF) associated or not with other organic dysfunction, with a high mortality rate. We report the characteristics and evolution of severe leptospirosis associated with ARF. During 10 years, 35 consecutive adult patients admitted in two general Intensive Care Units with severe leptospirosis and ARF, were followed up. Clinical characteristics, associated organic dysfunction and mortality were analyzed. Survivors were compared with non-survivors. The most frequent clinical manifestations were dyspnea, fever, myalgia, jaundice, hemoptysis and coughing. All patients presented ARF, needing mechanical ventilation, as well as other organic dysfunctions. The mortality rate was 51%. Non-survivors were older and had a higher incidence of organic dysfunction, mainly renal, cardiovascular and neurological failures, as well as a higher level of acidosis. In conclusion, leptospirosis should be considered as a cause of severe ARF and other associated organic dysfunctions.